1995
DOI: 10.1002/micr.1920161103
|View full text |Cite
|
Sign up to set email alerts
|

Free flap monitoring: A review of current practice

Abstract: Individual techniques for the postoperative monitoring of free flaps vary considerably. In order to establish the currently preferred protocols, a survey was conducted among micro-surgeons in North America using a mailed questionnaire. Data were received from 95 centers for the monitoring of 2,825 free flaps performed during 1994. Results indicate that rates for flap salvage and overall success with free tissue transfer are closely related to surgical experience (number of cases performed per month). Ninety pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 14 publications
1
66
0
7
Order By: Relevance
“…Detection requires constant vigilance in the perioperative period, and clinical acumen remains the predominate monitoring technique, relying on assessment of colour, capillary refill, surface temperature and pinprick bleeding, if indicated (1-4). Nevertheless, adjunctive monitoring devices are also used frequently and have proved to be invaluable, even with experienced recovery personnel (2). The ideal monitor should be objective, provide a continuous recording of perfusion and show immediate recognition of anastomotic occlusion, and all events must be easily interpretable (1,5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Detection requires constant vigilance in the perioperative period, and clinical acumen remains the predominate monitoring technique, relying on assessment of colour, capillary refill, surface temperature and pinprick bleeding, if indicated (1-4). Nevertheless, adjunctive monitoring devices are also used frequently and have proved to be invaluable, even with experienced recovery personnel (2). The ideal monitor should be objective, provide a continuous recording of perfusion and show immediate recognition of anastomotic occlusion, and all events must be easily interpretable (1,5).…”
mentioning
confidence: 99%
“…Doppler ultrasound or laser Doppler flowmetry have universally become the most commonly used complements to conventional monitoring (2). We use laser Doppler flowmetry to monitor all of our microsurgical composite tissue transfers, beginning intraoperatively, to prevent kinking or stretching of the vascular pedicle, or excessive tension in flap closure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Successful salvage rates range from 28% to over 90%. (3,4,7,14,15) The rates vary depending upon the etiology, timing of salvage and experience of the centre. In a review of 150 cases Hidalgo (8) suggested that attempted salvage of compromised flaps significantly increases flap survival rates and recommended an aggressive approach towards early exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted among microsurgeons from 95 centers in North America revealed that 90% of microsurgeons use monitoring devices for monitoring of free-tissue transfer. 3 Several techniques were reported, but there is still no consensus as to which will eventually become the standard accepted method.…”
mentioning
confidence: 99%